Treasures of the Southern Sky - Gendler, Robert; Christensen, Lars Lindberg; Malin, David (Springer New York : Imprint: Springer, 2011)
In these pages, the reader can follow the engaging saga of astronomical exploration in the southern hemisphere, in a modern merger of aesthetics, science, and a story of human endeavor. This book is truly a celebration of southern skies.  Jerry Bonnell, Editor - Astronomy Picture of the Day The southern sky became accessible to scientific scrutiny only a few centuries ago, after the first European explorers ventured south of the equator. Modern observing and imaging techniques have since revealed what seems like a new Universe, previously hidden below the horizon, a fresh astronomical bounty of beauty and knowledge uniquely different from the northern sky. The authors have crafted a book that brings this hidden Universe to all, regardless of location or latitude. Treasures of the Southern Sky celebrates the remarkable beauty and richness of the southern sky in words and with world-class imagery. In part, a photographic anthology of deep sky wonders south of the celestial equator, this book also celebrates the human story of southern astronomy with an engaging and detailed history of key contributors to southern sky exploration. The accompanying text provides the reader with intriguing facts and useful information about the featured objects. The volume is arranged by southern hemisphere season and brings to the printed page many of the most provocative and beautiful astronomical images of our time, many in print for the first time. The collection of imagery covers a full range of deep sky astronomical objects, including the familiar and iconic as well as those that are more obscure but no less intriguing. Masterful, state of the art professional and amateur astrophotography highlights the authors' carefully selected deep sky "treasures." DUST JACKET: The beauty and richness of the southern night sky is legendary. From southern latitudes the finest globular clusters in the sky are visible to the unaided eye, as are the nearest galaxies, the Magellanic Clouds. The brightest part of the Milky Way passes overhead during the southern winter and the nearest bright star as well as the legendary asterism known as the Southern Cross are both observable throughout the year. Despite these stunning highlights, the southern sky has received has received less attention than its northern counterparty, and fewer photographs exist of its lesser known, yet equally stunning and intriguing objects. This visual anthology features striking photographic portraits of the most celebrated to the more obscure southern astronomical objects. Carefully selected world-class images have been assembled using the latest digital methods, revealing these southern gems in ways never before seen. To provide a context, the pictures capture the sky in variety of scales, from the wide vistas seen through hobby telescopes to the tiny fields relayed in exquisitely rich detail by the powerful optics of the largest professional telescopes, including the Hubbel Space Telescope and ESO's telescopes. The beauty of the night sky is on display in vivid color and dazzling detail. The presentation is further enhanced by a detailed history of southern sky exploration and lucid text that describes the southern night-sky wonders in ways that are engaging and non-technical.